2007
DOI: 10.1038/sj.npp.1301344
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Antagonists Counteract Sensorimotor Gating Deficits in the Phencyclidine Model of Psychosis

Abstract: Clinical and laboratory findings suggest that cannabinoids and their receptors are implicated in schizophrenia. The role of cannabinoids in schizophrenia remains however poorly understood, as data are often contradictory. The primary aim of this study was to investigate whether the cannabinoid CB1 receptor antagonists rimonabant and AM251 are able to reverse deficits of sensorimotor gating induced by phencyclidine and to mimic the 'atypical' antipsychotic profile of clozapine. The prepulse inhibition (PPI) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 78 publications
(91 reference statements)
3
32
1
Order By: Relevance
“…However, whether endocannabinoid levels are altered in rats as a result of social isolation remains an open question. Interestingly, we (Malone et al, 2004) and others (Ballmaier et al, 2007) have shown that PPI gating deficits induced by drugs such as apomorphine can be reversed by pretreatment with the CB 1 receptor antagonist SR 141716 (rimonabant), implying that the endocannabinoid system has a role in modulating sensorimotor gating processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether endocannabinoid levels are altered in rats as a result of social isolation remains an open question. Interestingly, we (Malone et al, 2004) and others (Ballmaier et al, 2007) have shown that PPI gating deficits induced by drugs such as apomorphine can be reversed by pretreatment with the CB 1 receptor antagonist SR 141716 (rimonabant), implying that the endocannabinoid system has a role in modulating sensorimotor gating processes.…”
Section: Discussionmentioning
confidence: 99%
“…A full-blown psychosic episode developed with a latency of a few months following the discontinuation of rimonabant and despite being on antipsychotic treatment. These clinical observations contradict theoretical considerations that cannabinoid receptor antagonists unfold antipsychotic effects [10,11]. These theoretical considerations are widely supported by findings in rodents, which suggest a negative impact of rimonabant on dopamine D2 receptor-mediated neurotransmission [15] as well as functional and metabolic similarities between antipsychotics and rimonabant [16,17].…”
Section: Discussionmentioning
confidence: 53%
“…The psychotogenic effects are epidemiologically well established and may be due to the fact that agonists such as THC increase dopamine release [9]. Since rimonabant has an antagonistic impact on CB1 receptors, it decreases appetite [2] and may have antipsychotic propensities due to a decrease of the mesolimbic dopamine release [10]. However, a first trial of this hypothesis was not conclusive [11].…”
Section: Introductionmentioning
confidence: 92%
“…Notably, this gene has been associated with schizophrenia vulnerability in several studies [159,160]. While preclinical results have suggested that antagonism of CB 1 may attenuate schizophrenia symptoms [161,162], preliminary clinical trials have failed to support this possibility [163].…”
Section: Effects Of Meth and Cannabis On Schizophreniamentioning
confidence: 96%